Don't be afraid of black holes: Vacuum sponge and vacuum stent treatment of leaks in the upper GI tract—a case series and mini-review - Schäfer, Christian (Frontiers in Surgery, 2023)
The treatment of leaks in the upper gastrointestinal tract has been revolutionized by the advent of covered self-expanding metal stents (cSEMS), endoscopic vacuum therapy (EVT), and recently, vacuum stent therapy (VST). In this retrospective study, we report the experiences with EVT and VST at our institution. Patients and methods: Twenty-two patients (15 male, 7 female) with leaks in the esophagus, at the esophago-gastric junction or anastomotic leaks underwent EVT by placing a sponge connected to a negative pressure pump into or near the leak. VST was applied in three patients. Results: EVT led to closure of the leak in 18 of 22 Patients (82%). In 9 patients (41%), EVT was followed by application of a cSEMS. One patient (5%) died during the hospital stay due to an aorto-esophageal fistula near the leak, four others (18%) due to underlying disease. The stricture rate was 3/22 (14%). All three patients in whom VST was applied had closure of the leak and recovered. Reviewing the literature, we identified sixteen retrospective series of ten or more patients (n=610) with an overall closure rate for EVT of 84%. In eight additional retrospective observations, a comparison between the efficacy of EVT and cSEMS therapy was performed that revealed a success rate of 89% and 69%, respectively (difference not significant, chi-square test). For VST, two small series show that closure is possible in the majority of patients. Conclusion: EVT and VST are valuable options in the treatment of leaks in the upper gastrointestinal tract.